Atrioventricular Node Dysfunction in Adult Patient with Atrial Septal Defect: Focus on Pacemaker Management - Jomanzyah MUA., et al (ACI (Acta Cardiologia Indonesiana), 2017)
Atrioventricular Node Dysfunction in Adult Patient With Atrial Septal Defect: Focus on Pacemaker Management